A SERS Sensor Prepared via Electrostatic Self-Assembly of Ta4C3@AgNP Nanocomposites for Detection of Ziram - Kai Hua; Liang Li; Pei Liang (Biosensors, 2025)
MXenes are a class of two-dimensional materials exhibiting excellent surface-enhanced Raman scattering (SERS) performance. Currently, the SERS studies of MXenes have been primarily focused on those with M2X and M3X2 structural motifs. In order to expand the SERS sensing application based on MXenes, in this paper, a SERS sensor made of Ta4C3@AgNP nanocomposite material was fabricated by electrostatic self-assembly. Tests such as different concentrations of R6G probe molecules showed that the minimum detection limit of this SERS sensor was 10−8 M, demonstrating excellent sensitivity. When different test areas are selected, the relative error of intensity under the same wave number is less than 10.7%, showing good repeatability and consistency. Furthermore, the Ta4C3@AgNP nanocomposite SERS sensor was used to detect the pesticide Ziram, and a quantitative model was established. Application detection indicates that this sensor has good sensitivity for the pesticide Ziram, and the minimum detection limit was 10−6 M, which exceeded national standard requirements. The findings of this study have potential application value in the fields of food safety and environmental protection.